2020
DOI: 10.3390/nu12103106
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of DHA on Language Development: A Review of Randomized Controlled Trials of DHA Supplementation in Pregnancy, the Neonatal Period, and Infancy

Abstract: This review summarizes randomized controlled trials (RCTs) assessing the effect of docosahexaenoic acid (DHA) supplementation in the first 1000 days on child language. Six databases were searched and RCTs were included if they involved supplementation with DHA during pregnancy, to preterm infants, or during the postpartum period, included a placebo group with less or no DHA, and reported a language outcome. We included 29 RCTs involving n = 10,405 participants from 49 publications. There was a total of 84 lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 126 publications
1
7
0
Order By: Relevance
“…Our review of the effect of a DHA intervention in the first 1000 days on behavioral development has a similar conclusion to reviews of DHA supplementation over the same period on cognition, motor or visual development [ 76 ], or language abilities [ 78 ]. Additionally, several reviews and meta-analyses of more specific windows within the first 1000 days have identified little, if any evidence of benefits of DHA supplementation for brain development [ 68 , 69 , 70 , 71 , 72 , 74 , 125 ].…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Our review of the effect of a DHA intervention in the first 1000 days on behavioral development has a similar conclusion to reviews of DHA supplementation over the same period on cognition, motor or visual development [ 76 ], or language abilities [ 78 ]. Additionally, several reviews and meta-analyses of more specific windows within the first 1000 days have identified little, if any evidence of benefits of DHA supplementation for brain development [ 68 , 69 , 70 , 71 , 72 , 74 , 125 ].…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, several reviews and meta-analyses of more specific windows within the first 1000 days have identified little, if any evidence of benefits of DHA supplementation for brain development [ 68 , 69 , 70 , 71 , 72 , 74 , 125 ]. Our previous review of DHA interventions and subsequent language abilities revealed that whilst the majority of language measures were null, four suggested a benefit and two suggested an adverse effect [ 78 ]. Differences in findings between RCTs of DHA supplementation and observational studies of dietary sources of DHA could be due to a number of reasons, such as additional nutrients present in foods naturally rich in DHA and the inherent confounding in observational studies due to the difficulty in adjusting for complex confounding factors [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous randomized controlled trials (RCTs) have attempted to evaluate the effect of providing supplemental DHA to pregnant women on child brain development through performance-based measures such as intelligence quotient tests. Multiple reviews of these RCTs have concluded very little evidence of an effect of a DHA intervention on cognition [ 15 , 16 , 17 , 18 ], executive functioning (higher-order cognitive abilities) [ 15 , 18 , 19 ], motor [ 15 , 16 , 17 , 18 ], or language abilities [ 15 , 16 , 17 , 18 , 20 ]; however, a recent review suggested some behavioral effects [ 21 ].…”
Section: Introductionmentioning
confidence: 99%